New Translational Insights on Metabolic Syndrome: Obesity, Hypertension, Diabetes and Beyond - Camille M. Balarini; Valdir A. Braga (Frontiers Media SA, 2021)
Metabolic syndrome (MetS) can be considered as a clustering of several risk factors such as obesity, hypertension, insulin resistance and dyslipidemia, which could lead to the development of diabetes and cardiovascular diseases (CVD). There are several underlying causes for MetS including overweight, physical inactivity and genetic factors. However, the underlying mechanisms that leads to MetS are still poorly understood. Therefore, the aim of this E-book is to provide a space where researchers holding different backgrounds could shed some light onto the pathophysiology of different risk factors involved in MetS, mostly from translational research worldwide.